PERLINDUNGAN HUKUM PEKERJA YANG MENGALAMI PEMUTUSAN HUBUNGAN KERJA AKIBAT MELAKUKAN PELANGGARAN BERSIFAT MENDESAK (Lex Jurnalica, 2021)
Juridical termination of employment relations can occur for several reasons. One of the reasons for the assignment of employment relations is regulated in Article 52 paragraph (2) of Government Regulation Number 35 of 2021 concerning Work Agreements for Certain Time, Outsourcing, Working Time and Rest Time, and the Commissioning of Employment Relations, namely urgent violations committed by workers. The purpose of this study is to analyze and find out the legal protection for termination of employment arrangements if workers commit violations with an urgent nature. The type of research used is normative legal research with a statutory approach and a conceptual approach. Government Regulation Number 35 of 2021 concerning Work Agreements for Certain Time, Outsourcing, Working Time and Rest Time, and the Commissioning of Employment Relations has basically not provided legal protection for workers. The regulation implies that employers will terminate their employment arbitrarily and there will be overlapping legal regulations with previous regulations. The legislators, especially implementing regulations, should pay attention to previous regulations so that there is no overlapping of rules and provides more legal certainty to subjects regulated in a regulation.Keywords: Urgent violation, Termination of employment, Legal protection.